2022
DOI: 10.21831/economia.v18i2.42790
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digitalization on MSMEs’ Financial Performance: The Mediating Role of Dynamic Capability

Abstract: The COVID-19 pandemic has negatively affected the 82.9% of MSMEs. They experienced a significant decrease in operating profit due to fixed production costs or increased production costs while the sales declined. Therefore, it requires various strategies to boost the financial performance of MSMEs through digitalization and dynamic capability. The sample consisted of 282 respondents from MSMEs in Central Java which then all primary data were processed using structural equation model analysis. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(62 reference statements)
0
7
0
1
Order By: Relevance
“…The fourth previous discussion on how this study expands the knowledge also explains the novelty of this study, considering that studies on the drivers and barriers to MSMEs' e-readiness in Indonesia so far have focused on identifying the drivers and barriers of MSMEs' e-readiness. This study's findings are considered to be economically significant, considering that it has been empirically proven that digitization will have a significant effect specifically on the financial performance of MSMEs (Indriastuti and Kartika 2022;Gunawan and Somantri 2023), MSMEs' revitalization (Putri and Asyari 2023), and in general on the national economy (Nata et al 2022). The level of e-readiness of MSMEs determines the success of the digitization process, which will provide advantages for MSMEs, especially from an economic point of view.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The fourth previous discussion on how this study expands the knowledge also explains the novelty of this study, considering that studies on the drivers and barriers to MSMEs' e-readiness in Indonesia so far have focused on identifying the drivers and barriers of MSMEs' e-readiness. This study's findings are considered to be economically significant, considering that it has been empirically proven that digitization will have a significant effect specifically on the financial performance of MSMEs (Indriastuti and Kartika 2022;Gunawan and Somantri 2023), MSMEs' revitalization (Putri and Asyari 2023), and in general on the national economy (Nata et al 2022). The level of e-readiness of MSMEs determines the success of the digitization process, which will provide advantages for MSMEs, especially from an economic point of view.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, several types of industries were involved; however, this study did not control the industrial effects. Third, previous studies have focused on industry per region; for example, Putri and Asyari (2023) conducted a study for MSMEs in Bukittinggi, Indriastuti and Kartika (2022) focused on studies for the Central Java region. In this study, the research was focused on three provinces in Java Island, including West Java, Central Java, and East Java.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on the effect of digitalization on business performance through competitive advantage say that there is a mediating role for competitive advantage in the positive relationship between digitalization and business performance, as research conducted by Yuliantari & Pramuki explained that competitive advantage has a mediating role in the effect of digitalization on the performance of an MSME [23]. Other studies conducted by Indriastuti & Kartika have also found the same thing that competitive advantage has a mediating role in the effect of digitalization on business performance [29] the hypothesis can be drawn as follows:…”
Section: H2: Digitalization Has a Positive Effect On The Competitive ...mentioning
confidence: 93%
“…Banyak UMKM memiliki peluang untuk beralih dari perdagangan tradisional ke tren baru yang menerapkan teknologi karena digitalisasi memungkinkan mereka untuk mempromosikan produk dan layanan mereka melalui platform digital, baik dalam bentuk gambar dan video. Selain itu, mereka membuat toko daring pada marketplace untuk memudahkan pelanggan menemukan produk mereka (Indriastuti & Kartika, 2022).…”
Section: Pendahuluanunclassified